The Effects of Runaway-Homeless Episodes on High School Dropout. (March 2015) - Aratani, Yumiko; Cooper, Janice L.
This article uses data from the National Longitudinal Survey of Youth 1997 to examine the relationship between running away from home between the ages of 12 and 14 and dropping from high school among youth. Propensity score matching was conducted in estimating the effect of running away on high school dropout while controlling for confounding factors, such as familial instability and socioemotional health risks. The findings suggest that having runaway-homeless episodes have a detrimental effect on academic achievement.